Analysis of neuroendoscopy for the treatment of macroadenomas and giant pituitary adenomas - Wu, Junyong; Zhang, Binbin; Shao, Dongqi; Ji, Shuxin; Li, Yu; Xie, Shan; Jiang, Zhiquan (Frontiers in Surgery, 2022)
Abstract Objective: This study investigated the use and effectiveness of endoscopic transnasal, transsphenoidal surgery, a minimally invasive method for the treatment of macroadenomas and giant pituitary a denomas, in a medical setting. The surgical results of 429 patients who received neuroendoscopic treatment of macroadenomas or giant pituitary adenomas were evaluated, and the experiences and lessons learned from treatment complications were assessed. Patients and Methods: From January 2012 to December 2021, 429 patients with macroadenomas or giant pituitary adenomas, including 60 patients with giant adenomas (diameter ≥4 cm) and 369 patients with macroadenomas (diameter 1–4 cm), received a 3D head CT, a MRI with contrast enhancement, and an endocrinology examination prior to surgery. Preoperative clinical and radiological features, visual measurements, hormone levels, length of stay, length of surgery, postoperative stay, visual and hormone outcomes, resection range, complication and recurrence rates, and routine patient information were recorded. The patients were followed up for 6–72 months (median=40 months). Results: Of 429 patients with macroadenomas or giant pituitary adenomas who received neuroendoscopic treatment, 348 (81.12%) had gross-total resections (GTR), 53 (12.35%) had near-total resections (NTR), and 28 (6.53%) had subtotal resections. There were 138 cases of post-operative diabetes insipidus (32.17%), including 7 cases of permanent diabetes insipidus (1.63%), 16 cases of nasal hemorrhage (3.73%), 39 cases of intraoperative cerebrospinal fluid leakage (9.09%), 4 cases of intracranial infection (0.9%), 16 cases of hypophysis (3.7%), and 15 cases of anosmia (3.50%). The clinical symptoms and endocrinology indices of the patients improved after surgery, and all patients were discharged 5–18 days (8.36 ± 2.65) postop. Conclusion: Neuroendoscopy is a safe operation with a short recovery period and hospital stay and is thus an effective method to treat macroadenomas and giant pituitary adenomas. Preoperative evaluation and prediction can help to accurately address possible intraoperative situations and improve GTR. Keywords: neuroendoscopy; transnasal butterfly approach; macroadenoma; giant pituitary adenoma; pituitary surgery